MANAJEMEN PENGENDALIAN MUTU DI SEKOLAH MENENGAH KEJURUAN (SMK) CENDEKIA KOTA MADIUN - Sedya Santosa; Ahmad Mushthofa (Idaarah: Jurnal Manajemen Pendidikan, 2022)
The research that the researchers conducted tried to improve control management, in order to describe the quality of educational institutions at SMK Cendekia Madiun, then to analyze the control of a school quality to maintain the quality of education according to the plans that have been determined and written at SMK Cendekia Madiun. The research approach used ethology or human ethology, which is qualitative which aims to study its natural condition. Sources of data in this study amounted to 3 positions of informants, principals, managerial supervisors, teachers. Data collection is by observation, interviews, and documentation. This research uses source triangulation analysis as a validity test. From the results of this study indicate that in quality control includes: determining the education plan in the form of drawing up the vision, mission and objectives as well as RKAS. Second, measuring the real performance of educational institutions including curriculum, environmental and cultural determination, student control, careful planning of sarpras, effective leadership and giving good examples to teachers and students. Third, objectively monitoring and evaluation of educational institutions.